Heat-resistant ammonium polyphosphate with ultrahigh polymerization degree and synthesis method thereof

By improving the initial polymerization degree of ammonium polyphosphate and performing modification treatment, combined with end capping and coating technology, the problem of insufficient heat and moisture resistance and hot water resistance in high-end applications is solved, and stable application in hot and humid environments is achieved.

CN119877289APending Publication Date: 2025-04-25SHIFANG TAIFENG NEW FLAME RETARDANT

Patent Information

Application Number
CN202510076413.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing ammonium polyphosphate has problems in high-end applications with low initial decomposition temperature, high solubility in water, insufficient heat and humidity resistance and hot water resistance, which limits its application in high-end fields.

Method used

By adopting a synthetic method, an ammonium polyphosphate is increased by increasing the initial polymerization degree of ammonium polyphosphate and after modification treatment, the end capping treatment is performed using a coupling agent with epoxy groups, and then precuring and coating with an aqueous epoxy resin and a curing agent to form an ultra-high polymerization degree and heat-resistant ammonium polyphosphate.

Benefits of technology

The application capability of ammonium polyphosphate in hot and humid environments has been improved, especially under water soaking conditions at 80°C, the product does not precipitate or migrate, ensuring the stability of flame retardant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses heat-resistant ammonium polyphosphate with ultrahigh polymerization degree and a synthesis method thereof. The method comprises the following steps: (1) preparing ammonium polyphosphate: S1, mixing phosphorus pentoxide and diammonium hydrogen phosphate, stirring to react, and introducing ammonia gas to react; s2, mixing phosphoric acid with melamine for reaction, supplementing phosphoric acid, and stirring for reaction; s3, when the temperature in the first-step reaction is 280-300 DEG C, stopping introducing the ammonia gas, adding a product obtained in the step S2, supplementing diammonium hydrogen phosphate, and introducing the ammonia gas to continue the reaction; (2) end sealing; (3) pre-curing; and (4) mixing and dissolving epoxy resin and a curing agent, and then coating the surface of the pre-cured ammonium polyphosphate with the mixture. The initial polymerization degree of the ammonium polyphosphate can be improved, the initial molecular weight of the ammonium polyphosphate is higher, the application capacity of the ammonium polyphosphate in a humid and hot environment can be improved after modification treatment, especially when the ammonium polyphosphate is soaked in hot water at the temperature of 80 DEG C for 4 h, the product does not separate out or migrate, and the stability of the flame-retardant effect of the product is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of compound synthesis, and particularly relates to heat-resistant ammonium polyphosphate with ultra-high polymerization degree and a synthesis method thereof. Background Art

[0002] Ammonium polyphosphate (APP) is a phosphorus-nitrogen-containing, halogen-free, non-toxic additive flame retardant widely used in various flame retardant systems. In the field of textiles, APP is often added to flame retardants as an acid source, especially when back-coating various industrial or household textiles such as tents, curtains, sofa fabrics, seat fabrics, carpets, tablecloths, etc. However, APP used as a flame retardant still has problems such as low initial decomposition temperature, high solubility in water, and lack of heat and moisture resistance and hot water resistance, which limits its application in high-end fields.

[0003] According to comprehensive literature reports, the methods to reduce the solubility of APP in water and improve the compatibility of APP with polymer substrates and heat and moisture resistance mainly include increasing the degree of polymerization of APP, using surface resin microencapsulation and surfactant modification.

[0004] For example, the patent "CA1255448" uses isocyanate microencapsulation to treat APP; however, the viscosity of the modified product increases during the modification process, resulting in difficulties in microencapsulation processing. The patent "US6251961" uses melamine formaldehyde resin to microencapsulate APP; although the solubility in water is significantly reduced, the phosphorus and nitrogen content of the product are also significantly reduced. At the same time, formaldehyde is used in the reaction process, and free formaldehyde is easily present in the reaction product. At the same time, the wall material has limited compatibility with various materials. The patent "US5576391" uses melamine derivatives to microencapsulate APP; although the solubility in 60°C water drops from 65wt% to 10.4wt%, the solubility drops by 84%, but the phosphorus content drops by 29%. The treatment process is a multi-step reaction of low temperature and elevated temperature, the treatment time is as long as 10h, and a large amount of dichloromethane toxic solvent is also used. The patent "US5071901" uses anionic surfactants to modify APP, but its solubility in water does not change much. Chen Wenyan, Liu Xinchun, Liu Gousheng, and Yu Jianguo, in the article "Synthesis and Characterization of Crystalline Type V Ammonium Polyphosphate with Network Structure", used 85% of food-grade phosphoric acid as raw material and melamine as condensation agent, and introduced wet ammonia gas to shrink and polymerize with excess phosphoric acid in the reaction system to synthesize a crystallized type V ammonium polyphosphate with a network structure, and the residual carbon rate at 700℃ was 53.6%. Xie Sizheng, Liu Huaxia, and Li Zhangwu, in the article "Preparation and Application Research of Crystalline Type II Ammonium Polyphosphate with High Polymerization Degree", used phosphorus pentoxide, diammonium hydrogen phosphate, and liquid ammonia as the main raw materials to prepare high-polymerization crystallized type II ammonium polyphosphate under certain process conditions. Melamine was added in the later stage of the reaction to play a role in the end-capping of ammonium polyphosphate. Hao Dongmei used conventional epoxy resin 7% E51 to treat APP in "The Effect of EP Microencapsulated APP on the Flame Retardant Properties of PP", and the water resistance of APP was improved, but the improvement effect was not obvious.

[0005] In applications with relatively high requirements, the above-mentioned modification method still cannot fully meet customer requirements, and there are still many defects. For example, when the environmentally friendly flame-retardant coating agent composed of the existing high-polymerization degree APP is made into a flame-retardant coated fabric, it encounters problems such as "frosting" and insufficient strength caused by migration in normal temperature or hot and humid environment. For example: The Chinese invention patent with application number "202110708820.6" discloses a method for preparing core-shell silica-coated nano-calcium carbonate; the invention coats the surface of the nano-calcium carbonate with a layer of silica sol extracted by water, thereby improving the acid resistance of the nano-calcium carbonate, and then performs surface treatment with a coupling agent and an organic acid to improve the dispersibility of the product in the polymer. However, the silica coating method used in the invention is not suitable for the coating of polyphosphoric acid amine. Therefore, in order to solve the problems of "frosting" and insufficient strength caused by migration, it is necessary to explore an effective APP method.

[0006] Patent "CN101760049A" discloses a method for preparing core-shell silica-coated APP. This method uses the excellent hydrophobicity, heat resistance, and high strength of silica to further solve the problems of APP's penetration migration, affecting the strength of products, and insufficient heat resistance. Patent "CN101235221A" discloses a method for preparing aminosilane coupling agent-modified APP. This method provides a surface organic modification technology that significantly reduces the water solubility of APP and improves the compatibility and flame retardant efficiency of APP expansion flame retardant polymer materials. The modified APP was applied to expansion flame retardant polypropylene, and the elongation at break and tensile strength were increased by 39.4% and 8.0%, respectively. The modification scheme uses inert solvents such as aromatic hydrocarbons and alcohols as solvents. Lin Zhuoshi's "Preparation of epoxy resin-coated ammonium polyphosphate composite flame retardant polypropylene and its thermal degradation kinetics" used E51 to coat APP in an ethanol system, and its water solubility dropped to 0.2 at the lowest, indicating that the coating was not dense enough. In the article "Preparation and Characterization of Epoxy Resin Encapsulated Ammonium Polyphosphate Microcapsules", Liu Lin from Tongji University used E44 to encapsulate APP. The solubility of APP at room temperature and 80°C was 0.49 and 3.7, respectively, indicating that the encapsulation effect was not ideal. In the article "Study on Double-layer Encapsulated Ammonium Polyphosphate and Its Flame-retardant PP", Yu Shouwu used melamine formaldehyde resin and epoxy resin to encapsulate APP in double layers, and used a water plus ethanol system to encapsulate APP respectively, with the lowest solubility of 0.08. The above-mentioned epoxy encapsulated APP processes basically adopted the in-situ polymerization method of the ethanol system, and the encapsulation effect was not particularly ideal.

[0007] In summary, the solutions described in the above literature cannot make APP have the characteristics of long-term resistance to hot water immersion, especially the high-standard application scenario that many actual customers now require that the textile coating be immersed in 80℃ for 4 hours without migration or precipitation. Summary of the invention

[0008] In view of the above-mentioned deficiencies in the prior art, the present invention provides an ammonium polyphosphate with ultra-high polymerization degree and heat resistance and a synthesis method thereof. The present invention can improve the initial polymerization degree of ammonium polyphosphate to make its initial molecular weight higher. In addition, the application ability of ammonium polyphosphate in a hot and humid environment can be improved after modification treatment, especially under special high requirements. The product can be immersed in hot water at 80°C for 4 hours without precipitation or migration, thereby ensuring the flame retardant stability of the product.

[0009] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:

[0010] A method for synthesizing heat-resistant ammonium polyphosphate with ultra-high polymerization degree comprises the following steps:

[0011] (1) Preparation of ammonium polyphosphate

[0012] S1. First step reaction: Mix phosphorus pentoxide and diammonium hydrogen phosphate, stir and react at 200-250℃ for 1-3h, and then heat to less than 4m 3 / h of ammonia gas is introduced, and the reaction is continued for not less than 6h; wherein, the ammonia gas is introduced in two stages, and the ventilation volume in the first stage is 1 / 4 to 1 / 3 of that in the second stage;

[0013] S2, second step reaction: phosphoric acid and melamine are mixed, reacted at 200-220°C for 0.5-1h, then phosphoric acid is added, and stirring reaction is continued at 220-250°C for 1.5-2h;

[0014] S3, when the temperature in the first step reaction rises to 280-300°C, stop introducing ammonia, add the product of the second step reaction to the first step reaction, add diammonium hydrogen phosphate, and continue to react for 4-10 hours by introducing ammonia;

[0015] (2) End-capping

[0016] The prepared ammonium polyphosphate is end-capped with a coupling agent having an epoxy group;

[0017] (3) Pre-curing

[0018] A coupling agent with amino group is used as a curing agent, and after mixing it with the blocked ammonium polyphosphate and the waterborne epoxy resin, it is heated at 40-45°C to complete pre-curing;

[0019] (4) Coating

[0020] The epoxy resin and the curing agent are mixed and dissolved, and then coated on the surface of the pre-cured ammonium polyphosphate, and dried after the solvent evaporates to obtain an ultra-high degree of polymerization and heat-resistant ammonium polyphosphate. Furthermore, in step (1), the mass ratio of phosphorus pentoxide to diammonium hydrogen phosphate is 1:1 to 1:3.

[0021] Furthermore, in step S1, the mass ratio of phosphorus pentoxide to diammonium hydrogen phosphate is 1:1.

[0022] Furthermore, in step S1, the initial reaction temperature is 220° C., and the reaction temperature increases as the reaction progresses.

[0023] Furthermore, in step S1, after reacting at 220° C. for 1 hour, ammonia gas is introduced.

[0024] Furthermore, the introduction of ammonia in step S1 is divided into two stages. The first stage is the initial 0.5 to 1 hour of introduction of ammonia, followed by the second stage of introduction of ammonia, and the amount of ammonia introduced in the second stage is greater than that in the first stage.

[0025] Furthermore, the amount of ammonia introduced in the first stage is 0.8 to 1.2 m 3 / h, the amount of ammonia introduced in the second stage is 3~3.5m 3 / h.

[0026] Furthermore, the amount of ammonia introduced in step S3 is 3 to 3.5 m 3 / h, which is consistent with the ammonia introduction amount in the second stage in step S1.

[0027] Furthermore, the phosphoric acid initially added in step S2 is 12.3% of the mass of phosphorus pentoxide in step S1, and the molar ratio of phosphorus pentoxide to melamine is 1:3.

[0028] Furthermore, the amount of phosphoric acid supplemented in step S2 is the same as the amount of phosphoric acid initially added.

[0029] Furthermore, in step S2, the initial reaction temperature is 200°C, the reaction time is 0.5h, and after phosphoric acid is added, the temperature is raised to 220°C to continue the reaction.

[0030] Further, the process of end-capping is:

[0031] The APP powder is capped by adding a coupling agent with epoxy groups in an amount of 1 to 2% of the total mass of the APP powder.

[0032] Furthermore, the coupling agent with epoxy group is KH560.

[0033] Furthermore, the strongly active coupling agents with amino groups are KH540 and KH550, and the mass ratio of the coupling agents to the waterborne epoxy resin is 1:1.

[0034] Furthermore, the epoxy resin used in step (4) is tetraepoxycyclohexylcyclosiloxane or AG-80; and the curing agent is a polyamide curing agent.

[0035] Furthermore, in step (4), the mass ratio of epoxy resin to curing agent is 1:1.

[0036] The invention discloses heat-resistant ammonium polyphosphate with ultra-high polymerization degree, which is synthesized by the method described above.

[0037] Beneficial effects of the present invention:

[0038] In the early stage of ammonium polyphosphate synthesis, a certain proportion of phosphoric acid and melamine reaction crosslinking body is added to make the ammonium polyphosphate crystal have a certain network structure in the early stage of synthesis, so as to improve the final polymerization degree of the product; subsequently, a common coupling agent with epoxy group activity is firstly used to perform end-capping treatment on the ammonium polyphosphate product, and then a resin prepolymer with special heat and moisture resistance is used to coat the modified ammonium polyphosphate.

[0039] The present invention constructs a synthesis process of ultra-high polymerization degree ammonium polyphosphate, and the synthesis process is divided into two parts. The main reactor (first step reaction) initially synthesizes APP with a certain chain length. At the same time, low ammonia is introduced at the initial stage of the reaction to make the initial crystals of the synthesized APP larger. The secondary reactor (second step reaction) initially constructs melamine phosphate with melamine as the core. Excess phosphoric acid is added in the later stage of the secondary reaction to extend the phosphoric acid molecular chain, which is convenient for the next step and the main reaction to carry out a long-chain reaction. Here, the main reaction needs to control the temperature to 280-300° C. so that the subsequent reaction can be completed as planned; and then appropriate diammonium hydrogen phosphate is added to react the excess phosphoric acid, and finally a macromolecular ammonium polyphosphate with melamine as the center is synthesized.

[0040] The present invention changes the long-standing scheme of using melamine to end-cap APP, and uses a coupling agent containing epoxy for end-capping, which is conducive to the implementation of the later coating reaction. In the implementation scheme of the coating scheme, water-based epoxy resin (non-emulsified system) and unconventional curing agent are used, and unconventional epoxy resin with strong heat and moisture resistance and resin curing agent are used in the later stage of the reaction. The product has strong water resistance after curing, and the curing adopts airflow curing, which has no destructive effect on APP. The coating system is a link between the above and the following, and is closely linked. DETAILED DESCRIPTION

[0041] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0042] Example 1

[0043] A method for synthesizing heat-resistant ammonium polyphosphate with ultra-high polymerization degree comprises the following steps:

[0044] (1) Preparation of ammonium polyphosphate

[0045] S1. Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir the reaction for 1.0h, and slowly introduce ammonia. Use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction. 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled to 3m 3 / h, continue the reaction for 8h;

[0046] S2, take another 2L strong stirring equipment (reaction secondary equipment), set the initial temperature to 220°C, add 0.162kg 85% phosphoric acid, then add 0.059kg melamine, react for 0.5h, then continue to add 0.162kg phosphoric acid, continue heating and stirring to react for 2h;

[0047] S3, the temperature of the main reaction material rises to 285℃, the ammonia is stopped, the reactants of the secondary reaction equipment are transferred to the main reaction equipment, and 0.093kg of diammonium hydrogen phosphate is added, dispersed and stirred for 15 minutes, and then 3m 3 / h of ammonia to react for 4h; take samples to test the degree of polymerization;

[0048] (2) End-capping

[0049] Open the lid and spray 0.062kg of KH560 that has been hydrolyzed by mixing ethanol and water for 10 hours in advance; crush the generated ammonium polyphosphate (APP) to test its solubility;

[0050] (3) Pre-curing

[0051] Take 0.03 kg of water-based hydantoin epoxy, disperse and dissolve it in water, add 0.03 kg of KH540 with strong amino hydrolysis activity, heat the reaction temperature to 45 ° C, pre-cure the epoxy resin system for 3 hours, filter, and wash with ethanol;

[0052] (4) Coating

[0053] Then, the powder preliminarily modified after the treatment in step (3) is added to a spray drying tower with an initial temperature of 100°C, and stirred and dried for 0.5h. 0.03kg of epoxy resin tetraepoxycyclohexylcyclosiloxane with excellent heat and moisture resistance and 0.03kg of polyamide curing agent are dispersed together in 0.06kg of ethanol, heated to 50°C, and then sprayed into the spray drying tower at a uniform speed for 10min. After the solvent evaporates, it is transferred to a 150°C drying double hammer and continued to dry for 5h before discharging, thereby obtaining the ultra-high polymerization degree and heat-resistant ammonium polyphosphate.

[0054] Example 2

[0055] A method for synthesizing heat-resistant ammonium polyphosphate with ultra-high polymerization degree comprises the following steps:

[0056] (1) Preparation of ammonium polyphosphate

[0057] S1. Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir and react for 1.0h, slowly introduce ammonia, and use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction to 1m 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled at 3.5m3 / h, reaction time 6h;

[0058] S2, take another 2L strong stirring equipment (reaction secondary equipment), set the initial temperature to 220°C, add 0.162kg 85% phosphoric acid, then add 0.059kg melamine, react for 0.5h, then continue to add 0.162kg phosphoric acid, continue heating and stirring to react for 1.8h;

[0059] S3, the temperature of the main reaction material rises to 282℃, the ammonia is stopped, the reactants of the secondary reaction equipment are transferred to the main reaction equipment, and 0.093kg of diammonium hydrogen phosphate is added, dispersed and stirred for 15 minutes, and then 3.5m 3 / h of ammonia gas was introduced to react for 4 hours; samples were taken to test the degree of polymerization;

[0060] (2) End-capping

[0061] Open the lid and spray 0.062kg of KH560 that has been hydrolyzed by mixing ethanol and water for 10 hours in advance; crush the generated ammonium polyphosphate (APP) to test its solubility;

[0062] (3) Pre-curing

[0063] Take 0.03 kg of water-based hydantoin epoxy, disperse and dissolve it in water, add 0.03 kg of KH540 with strong amino hydrolysis activity, heat the reaction temperature to 45 ° C, pre-cure the epoxy resin system for 3 hours, filter, and wash with ethanol;

[0064] (4) Coating

[0065] The powder preliminarily modified after the treatment in step (3) is added to a spray drying tower with an initial temperature of 100°C, stirred and dried for 0.5h, then 0.03kg of epoxy resin tetraepoxycyclohexylcyclosiloxane with excellent heat and moisture resistance and 0.03kg of polyamide curing agent are dispersed together in 0.06kg of ethanol, heated to 50°C, and then sprayed into the spray drying tower at a uniform speed for 10min; after the solvent evaporates, it is transferred to a 150°C drying double hammer and continued to dry for 5h before discharging to obtain the ammonium polyphosphate with ultra-high polymerization degree and heat resistance.

[0066] Example 3

[0067] A method for synthesizing heat-resistant ammonium polyphosphate with ultra-high polymerization degree comprises the following steps:

[0068] (1) Preparation of ammonium polyphosphate

[0069] S1. Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir and react for 1.0h, slowly introduce ammonia, and use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction to 1m3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled at 3.5m 3 / h, reaction time 10h;

[0070] S2, take another 2L strong stirring equipment (reaction secondary equipment), set the initial temperature to 220°C, add 0.162kg 85% phosphoric acid, then add 0.059kg melamine, react for 0.5h, then continue to add 0.162kg phosphoric acid, continue heating and stirring to react for 2.0h;

[0071] S3, the temperature of the main reaction material rises to 295℃, the ammonia gas is stopped, the reactants of the secondary reaction equipment are transferred to the main reaction equipment, and 0.093kg of diammonium hydrogen phosphate is added, dispersed and stirred for 15 minutes, and then continued at 3.5m 3 / h of ammonia gas was introduced to react for 4 hours; samples were taken to test the degree of polymerization;

[0072] (2) End-capping

[0073] Open the lid and spray 0.062kg of KH560 that has been hydrolyzed by mixing ethanol and water for 10 hours in advance; crush the generated ammonium polyphosphate (APP) to test its solubility;

[0074] (3) Pre-curing

[0075] Take 0.03 kg of water-based hydantoin epoxy, disperse and dissolve it in water, add 0.03 kg of KH540 with strong amino hydrolysis activity, heat the reaction temperature to 45 ° C, pre-cure the epoxy resin system for 3 hours, filter, and wash with ethanol;

[0076] (4) Coating

[0077] The powder preliminarily modified after the treatment in step (3) is added to a spray drying tower with an initial temperature of 100°C, stirred and dried for 0.5h, then 0.03kg of epoxy resin tetraepoxycyclohexylcyclosiloxane with excellent heat and moisture resistance and 0.03kg of polyamide curing agent are dispersed together in 0.06kg of ethanol, heated to 50°C, and then sprayed into the spray drying tower at a uniform speed for 10min; after the solvent evaporates, it is transferred to a 150°C drying double hammer and continued to dry for 5h before discharging to obtain the ammonium polyphosphate with ultra-high polymerization degree and heat resistance.

[0078] Example 4

[0079] A method for synthesizing heat-resistant ammonium polyphosphate with ultra-high polymerization degree comprises the following steps:

[0080] (1) Preparation of ammonium polyphosphate

[0081] S1. Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir and react for 1.0h, slowly introduce ammonia, and use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction to 1m 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled to 3.0m 3 / h, reaction time 7.5h;

[0082] S2, take another 2L strong stirring equipment (reaction secondary equipment), set the initial temperature to 220°C, add 0.162kg 85% phosphoric acid, then add 0.059kg melamine, react for 0.5h, then continue to add 0.162kg phosphoric acid, continue heating and stirring to react for 2.0h;

[0083] S3, the temperature of the main reaction material rises to 288℃, the ammonia is stopped, the reactants of the secondary reaction equipment are transferred to the main reaction equipment, and 0.093kg of diammonium hydrogen phosphate is added, dispersed and stirred for 15 minutes, and then 3.0m 3 / h of ammonia gas was introduced to react for 5 hours; samples were taken to test the degree of polymerization;

[0084] (2) End-capping

[0085] Open the lid and spray 0.062kg of KH560 that has been hydrolyzed by mixing ethanol and water for 10 hours in advance; crush the generated ammonium polyphosphate (APP) to test its solubility;

[0086] (3) Pre-curing

[0087] Take 0.03 kg of water-based hydantoin epoxy, disperse and dissolve it in water, add 0.03 kg of KH540 with strong amino hydrolysis activity, heat the reaction temperature to 45 ° C, pre-cure the epoxy resin system for 3 hours, filter, and wash with ethanol;

[0088] (4) Coating

[0089] The powder preliminarily modified after the treatment in step (3) is added to a spray drying tower with an initial temperature of 100°C, stirred and dried for 0.5h, then 0.03kg of epoxy resin tetraepoxycyclohexylcyclosiloxane with excellent heat and moisture resistance and 0.03kg of polyamide curing agent are dispersed together in 0.06kg of ethanol, heated to 50°C, and then sprayed into the spray drying tower at a uniform speed for 10min; after the solvent evaporates, it is transferred to a 150°C drying double hammer and continued to dry for 5h before discharging to obtain the ammonium polyphosphate with ultra-high polymerization degree and heat resistance.

[0090] Example 5

[0091] A method for synthesizing heat-resistant ammonium polyphosphate with ultra-high polymerization degree comprises the following steps:

[0092] (1) Preparation of ammonium polyphosphate

[0093] S1. Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir and react for 1.0h, slowly introduce ammonia, and use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction to 1m 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled at 3.5m 3 / h, reaction time 6.5h;

[0094] S2, take another 2L strong stirring equipment (reaction secondary equipment), set the initial temperature to 200°C, add 0.162kg 85% phosphoric acid, then add 0.059kg melamine, react for 0.5h, then continue to add 0.162kg phosphoric acid, continue heating and stirring to react for 2.0h;

[0095] S3, the temperature of the main reaction material rises to 300℃, the ammonia is stopped, the reactants of the secondary reaction equipment are transferred to the main reaction equipment, and 0.093kg of diammonium hydrogen phosphate is added, dispersed and stirred for 15 minutes, and then the temperature is continued at 3.5m 3 / h of ammonia gas was introduced to react for 4 hours; samples were taken to test the degree of polymerization;

[0096] (2) End-capping

[0097] Open the lid and spray 0.062kg of KH560 that has been hydrolyzed by mixing ethanol and water for 10 hours in advance; crush the generated ammonium polyphosphate (APP) to test its solubility;

[0098] (3) Pre-curing

[0099] Take 0.03 kg of water-based hydantoin epoxy, disperse and dissolve it in water, add 0.03 kg of KH540 with strong amino hydrolysis activity, heat the reaction temperature to 45 ° C, pre-cure the epoxy resin system for 3 hours, filter, and wash with ethanol;

[0100] (4) Coating

[0101] The powder preliminarily modified after the treatment in step (3) is added to a spray drying tower with an initial temperature of 100°C, stirred and dried for 0.5h, then 0.03kg of epoxy resin tetraepoxycyclohexylcyclosiloxane with excellent heat and moisture resistance and 0.03kg of polyamide curing agent are dispersed together in 0.06kg of ethanol, heated to 50°C, and then sprayed into the spray drying tower at a uniform speed for 10min; after the solvent evaporates, it is transferred to a 100°C drying double hammer and continued to dry for 8h before discharging to obtain the ammonium polyphosphate with ultra-high polymerization degree and heat resistance.

[0102] Example 6

[0103] A method for synthesizing heat-resistant ammonium polyphosphate with ultra-high polymerization degree comprises the following steps:

[0104] (1) Preparation of ammonium polyphosphate

[0105] S1. Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir the reaction for 1.0h, and slowly introduce ammonia. Use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction to 1.2m 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled to 3m 3 / h, reaction time 8.5h;

[0106] S2. Meanwhile, take another 2L strong stirring device (reaction secondary device), set the initial temperature to 220°C, add 0.162kg 85% phosphoric acid, then add 0.059kg melamine, react for 0.5h, then continue to add 0.162kg phosphoric acid, continue heating and stirring to react for 2h;

[0107] S3, the temperature of the main reaction material rises to 284℃, the ammonia is stopped, the reactants of the secondary reaction equipment are transferred to the main reaction equipment, and 0.093kg diammonium hydrogen phosphate is added, dispersed and stirred for 15 minutes, and then 3m 3 / h of ammonia gas was introduced to react for 4 hours; samples were taken to test the degree of polymerization;

[0108] (2) End-capping

[0109] Open the lid and spray 0.062kg of KH560 that has been hydrolyzed by mixing ethanol and water for 10 hours in advance; crush the generated ammonium polyphosphate (APP) to test its solubility;

[0110] (3) Pre-curing

[0111] Take 0.03 kg of water-based hydantoin epoxy, disperse and dissolve it in water, add 0.03 kg of KH540 with strong amino hydrolysis activity, heat the reaction temperature to 45 ° C, pre-cure the epoxy resin system for 3 hours, filter, and wash with ethanol;

[0112] (4) Coating

[0113] The powder preliminarily modified after the treatment in step (3) is added to a spray drying tower with an initial temperature of 100°C, stirred and dried for 0.5h, then 0.03kg of epoxy resin tetrafunctional glycidylamine (AG-80) with excellent heat and moisture resistance and 0.03kg of polyamide curing agent are dispersed together in 0.06kg of ethanol, heated to 50°C, and then sprayed into the spray drying tower at a uniform speed for 10min; after the solvent evaporates, it is transferred to a 150°C drying double hammer and continued to dry for 4h before discharging to obtain the ultra-high polymerization degree and heat-resistant ammonium polyphosphate.

[0114] Example 7

[0115] A method for synthesizing heat-resistant ammonium polyphosphate with ultra-high polymerization degree comprises the following steps:

[0116] (1) Preparation of ammonium polyphosphate

[0117] S1. Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir the reaction for 1.0h, and slowly introduce ammonia. Use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction to 0.8m 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled to 3m 3 / h, reaction time 8h;

[0118] S2, take another 2L strong stirring equipment (reaction secondary equipment), set the initial temperature to 220°C, add 0.162kg 85% phosphoric acid, then add 0.059kg melamine, react for 0.5h, then continue to add 0.162kg phosphoric acid, continue heating and stirring to react for 2h;

[0119] S3, the temperature of the main reaction material rises to 285℃, the ammonia is stopped, the reactants of the secondary reaction equipment are transferred to the main reaction equipment, and 0.093kg of diammonium hydrogen phosphate is added, dispersed and stirred for 15 minutes, and then 3m 3 / h of ammonia gas was introduced to react for 4 hours; samples were taken to test the degree of polymerization;

[0120] (2) End-capping

[0121] Open the lid and spray 0.062kg of KH560 that has been hydrolyzed by mixing ethanol and water for 10 hours in advance; crush the generated ammonium polyphosphate (APP) to test its solubility;

[0122] (3) Pre-curing

[0123] Take 0.03 kg of water-based hydantoin epoxy, disperse and dissolve it in water, add 0.03 kg of KH550 with amino group, heat the reaction temperature to 45°C, pre-cure the epoxy resin system for 3 hours, filter, and wash with ethanol;

[0124] (4) Coating

[0125] The powder preliminarily modified after the treatment in step (3) is added to a spray drying tower with an initial temperature of 100°C, stirred and dried for 0.5h, then 0.03kg of epoxy resin tetraepoxycyclohexylcyclosiloxane with excellent heat and moisture resistance and 0.03kg of polyamide curing agent are dispersed together in 0.06kg of ethanol, heated to 50°C, and then sprayed into the spray drying tower at a uniform speed for 10min; after the solvent evaporates, it is transferred to a 100°C drying double hammer and continued to dry for 8h before discharging to obtain the ammonium polyphosphate with ultra-high polymerization degree and heat resistance.

[0126] Example 8

[0127] A method for synthesizing heat-resistant ammonium polyphosphate with ultra-high polymerization degree comprises the following steps:

[0128] (1) Preparation of ammonium polyphosphate

[0129] S1. Set the initial temperature of the 5L kneader (main reaction equipment) to 200°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir the reaction for 1.0h, and slowly introduce ammonia. Use a precision flow meter to control the amount of ammonia in the initial 0.5h of the reaction. 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled to 3m 3 / h, reaction time 8h;

[0130] S2, take another 2L strong stirring equipment (reaction secondary equipment), set the initial temperature to 210°C, add 0.162kg 85% phosphoric acid, then add 0.059kg melamine, react for 0.5h, then continue to add 0.162kg phosphoric acid, continue stirring and reacting for 2h;

[0131] S3, the temperature of the main reaction material rises to 285℃, the ammonia is stopped, the reactants of the secondary reaction equipment are transferred to the main reaction equipment, and 0.093kg of diammonium hydrogen phosphate is added, dispersed and stirred for 15 minutes, and then 3m 3 / h of ammonia gas was introduced to react for 4 hours; samples were taken to test the degree of polymerization;

[0132] (2) End-capping

[0133] Open the lid and spray 0.062kg of KH560 that has been hydrolyzed by mixing ethanol and water for 10 hours in advance; crush the generated ammonium polyphosphate (APP) to test its solubility;

[0134] (3) Pre-curing

[0135] Take 0.03 kg of water-based hydantoin epoxy, disperse and dissolve it in water, add 0.03 kg of KH540 with strong amino hydrolysis activity, heat the reaction temperature to 45 ° C, pre-cure the epoxy resin system for 3 hours, filter, and wash with ethanol;

[0136] (4) Coating

[0137] The powder preliminarily modified after the treatment in step (3) is added to a fluidized bed furnace with an initial temperature of 100°C, and dried by stirring for 0.5h. Then, 0.03kg of epoxy resin tetraepoxycyclohexylcyclosiloxane with excellent heat and moisture resistance and 0.03kg of polyamide curing agent are dispersed together in 0.06kg of ethanol, heated to 50°C, and then sprayed into a spray drying tower at a uniform speed for 10min. After the solvent evaporates, it is transferred to a 150°C drying double hammer and continued to dry for 5h before discharging to obtain the ammonium polyphosphate with ultra-high polymerization degree and heat resistance.

[0138] Example 9

[0139] A method for synthesizing heat-resistant ammonium polyphosphate with ultra-high polymerization degree comprises the following steps:

[0140] (1) Preparation of ammonium polyphosphate

[0141] S1. Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir the reaction for 1.0h, and slowly introduce ammonia. Use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction. 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled to 3m 3 / h, reaction time 8.5h;

[0142] S2, take another 2L strong stirring equipment (reaction secondary equipment), set the initial temperature to 220°C, add 0.162kg 85% phosphoric acid, then add 0.059kg melamine, react for 0.5h, then continue to add 0.162kg phosphoric acid, continue heating and stirring to react for 2h;

[0143] S3, the temperature of the main reaction material rises to 284℃, the ammonia is stopped, the reactants of the secondary reaction equipment are transferred to the main reaction equipment, and 0.093kg diammonium hydrogen phosphate is added, dispersed and stirred for 15 minutes, and then 3m 3 / h of ammonia gas was introduced to react for 4 hours; samples were taken to test the degree of polymerization;

[0144] (2) End-capping

[0145] Open the lid and spray 0.062kg of KH560 that has been hydrolyzed by mixing ethanol and water for 10 hours in advance; crush the generated ammonium polyphosphate (APP) to test its solubility;

[0146] (3) Pre-curing

[0147] Take 0.03 kg of water-based hydantoin epoxy, disperse and dissolve it in water, add 0.03 kg of KH540 with strong amino hydrolysis activity, heat the reaction temperature to 45 ° C, pre-cure the epoxy resin system for 3 hours, filter, and wash with ethanol;

[0148] (4) Coating

[0149] The powder preliminarily modified after the treatment in step (3) is added to a spray drying tower with an initial temperature of 100°C, stirred and dried for 0.5h, then 0.03kg of epoxy resin tetrafunctional glycidylamine (AG-80) with excellent heat and moisture resistance and 0.03kg of polyamide curing agent are dispersed together in 0.06kg of ethanol, heated to 50°C, and then sprayed into the spray drying tower at a uniform speed for 10min; after the solvent evaporates, it is transferred to a 100°C drying double hammer and continued to dry for 6h before discharging to obtain the ultra-high polymerization degree and heat-resistant ammonium polyphosphate.

[0150] Example 10

[0151] A method for synthesizing heat-resistant ammonium polyphosphate with ultra-high polymerization degree comprises the following steps:

[0152] (1) Preparation of ammonium polyphosphate

[0153] S1. Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir the reaction for 1.0h, and slowly introduce ammonia. Use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction. 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled to 3m 3 / h, reaction time 7.5h;

[0154] S2. Meanwhile, take another 2L strong stirring device (reaction secondary device), set the initial temperature to 220°C, add 0.162kg 85% phosphoric acid, then add 0.059kg melamine, react for 0.5h, then continue to add 0.162kg phosphoric acid, continue heating and stirring to react for 2h;

[0155] S3, the temperature of the main reaction material rises to 285℃, the ammonia is stopped, the reactants of the secondary reaction equipment are transferred to the main reaction equipment, and 0.093kg of diammonium hydrogen phosphate is added, dispersed and stirred for 15 minutes, and then 3m 3 / h of ammonia gas was introduced to react for 4 hours; samples were taken to test the degree of polymerization;

[0156] (2) End-capping

[0157] Open the lid and spray 0.031kg of KH560 that has been hydrolyzed by mixing ethanol and water for 10 hours in advance; crush the generated ammonium polyphosphate (APP) to test its solubility;

[0158] (3) Pre-curing

[0159] Take 0.03 kg of water-based hydantoin epoxy, disperse and dissolve it in water, add 0.03 kg of KH540 with strong amino hydrolysis activity, heat the reaction temperature to 45 ° C, pre-cure the epoxy resin system for 3 hours, filter, and wash with ethanol;

[0160] (4) Coating

[0161] The powder preliminarily modified after the treatment in step (3) is added to a spray drying tower with an initial temperature of 100°C, stirred and dried for 0.5h, then 0.03kg of epoxy resin tetraepoxycyclohexylcyclosiloxane with excellent heat and moisture resistance and 0.03kg of polyamide curing agent are dispersed together in 0.06kg of ethanol, heated to 50°C, and then sprayed into the spray drying tower at a uniform speed for 10min; after the solvent evaporates, it is transferred to a 150°C drying double hammer and continued to dry for 5h before discharging to obtain the ammonium polyphosphate with ultra-high polymerization degree and heat resistance.

[0162] Comparative Example 1

[0163] Compared with Example 1, the difference is that the amount of ammonia introduced in the initial stage of the reaction in step S1 is 3m 3 / h, and the rest of the process is consistent with Example 1.

[0164] Comparative Example 2

[0165] Compared with Example 1, the difference is that the process of preparing ammonium polyphosphate is different, as follows:

[0166] Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir the reaction for 1.0h, and slowly introduce ammonia. Use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction. 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled to 3m 3 / h; continue to pass ammonia to react for 6h; take a sample to test the degree of polymerization, spray 0.062kg of KH560 that has been atomized and hydrolyzed by mixing ethanol and water for 10h in advance, and measure the solubility.

[0167] Comparative Example 3

[0168] Compared with Example 1, the difference is that the process of preparing ammonium polyphosphate is different, as follows:

[0169] Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.413kg of diammonium hydrogen phosphate, 0.324kg of 85% phosphoric acid, and 0.059kg of melamine, stir the reaction for 1.0h, and slowly introduce ammonia. Use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction. 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled to 3m 3 / h; continue to pass ammonia to react for 6h; take a sample to test the degree of polymerization, spray 0.062kg of KH560 that has been atomized and hydrolyzed by mixing ethanol and water for 10h in advance, and measure the solubility.

[0170] Comparative Example 4

[0171] Compared with Example 1, the difference is that after step (3) is completed, the material is directly transferred to a 150°C drying double hammer for further drying for 5.5 hours before being discharged. The rest of the process is consistent with Example 1.

[0172] Comparative Example 5

[0173] Set the initial temperature of the 5L kneader (main reaction equipment) to 220°C, add 1.32kg of phosphorus pentoxide and 1.32kg of diammonium hydrogen phosphate, stir the reaction for 1.0h, and slowly introduce ammonia. Use a precision flow meter to control the ammonia volume in the initial 0.5h of the reaction. 3 / h, so that the initial crystals of ammonium polyphosphate production are larger, and the ammonia volume is controlled to 3m 3 / h; at the same time, take another 2L strong stirring equipment (reaction secondary equipment), set the initial temperature to 220℃, add 0.162kg 85% phosphoric acid, then add 0.059kg melamine, react for 0.5h, then continue to add 0.162kg phosphoric acid, continue heating and stirring for 2h; the temperature of the main reaction material rises to 285℃, stop passing ammonia, transfer the reactants of the secondary reaction equipment to the main reaction equipment, and add 0.093kg diammonium hydrogen phosphate, disperse and stir for 15min, and continue to pass ammonia for 4h; take samples to test the degree of polymerization, and take a small amount of powder (10g) of powder to test the solubility of KH560 as in Example 1;

[0174] In the other part, 0.03kg of water-based hydantoin epoxy was dispersed and dissolved in water, and 0.03kg of KH540 with strong amino hydrolysis activity was added. The reaction temperature was heated to 45°C to pre-cure the epoxy resin system for 3 hours, and then filtered and washed with ethanol. Then the preliminarily modified powder was added to a spray drying tower with an initial temperature of 100°C, stirred and dried for 0.5 hours, and then 0.03kg of tetraepoxycyclohexylcyclosiloxane with excellent heat and moisture resistance and 0.03kg of polyamide curing agent were taken and dispersed in 0.06kg of ethanol, heated to 50°C, and then sprayed into the spray drying tower at a uniform speed for 10 minutes; after the solvent evaporated, it was transferred to a 150°C drying double hammer and continued to dry for 5 hours before discharging.

[0175] Comparative Example 6

[0176] Compared with Example 1, the difference is that the processing of step (3) is missing, and the rest of the process is consistent with Example 1.

[0177] Comparative Example 7

[0178] Compared with Example 1, the difference is that KH540 with strong amino hydrolysis activity as a curing agent is not added in step (3), and the rest of the process is consistent with Example 1.

[0179] Comparative Example 8

[0180] Compared with Comparative Example 7, the difference is that in step (4), epoxy resin tetrafunctional glycidylamine is used to replace tetraepoxycyclohexylcyclosiloxane, and the rest of the process is the same.

[0181] Comparative Example 9

[0182] The specific preparation process of the second type product currently produced by the enterprise is as follows:

[0183] The generated ammonium polyphosphate (APP) was crushed, 0.03kg of water-based hydantoin epoxy was taken, dispersed and dissolved in water, 0.03kg of KH540 with strong hydrolysis activity with amino group was added, the reaction temperature was heated to 45℃, the epoxy resin system was pre-cured for 3h, filtered, and washed with ethanol. Then the preliminarily modified powder was added to the spray drying tower with an initial temperature of 100℃, stirred and dried for 0.5h, and then 0.03kg of tetraepoxycyclohexylcyclosiloxane with excellent heat and moisture resistance and 0.03kg of polyamide curing agent were taken, dispersed in 0.06kg of ethanol, heated to 50℃, and then sprayed into the spray drying tower at a uniform speed for 10min; after the solvent evaporated, it was transferred to the 150℃ drying double hammer and continued to dry for 5h before discharging.

[0184] 1. The solubility and degree of polymerization of the samples prepared in the test examples and comparative examples were tested with reference to HG / T2770-2020. The specific test types and results are shown in Table 1.

[0185] Table 1 Solubility and degree of polymerization

[0186] Example 1 Example 2 Example 3 Example 4 Example 5 Initial solubility 0.21 0.25 0.29 0.17 0.18 Degree of Polymerization 3548 3420 2900 3902 3821 Solubility after modification 0.03 0.05 0.06 0.04 0.03 Example 6 Example 7 Example 8 Example 9 Example 10 Initial solubility 0.18 0.25 0.23 0.26 0.18 Degree of Polymerization 3899 3300 3520 3100 3888 Solubility after modification 0.03 0.04 0.04 0.05 0.04 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 9 Solubility 0.33 1.16 0.87 0.35 Degree of Polymerization 1300 50 110 1000 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Solubility before modification 0.22 0.22 0.22 0.22 0.22 Solubility after modification 0.12 0.10 0.12 0.09 0.08 Comparative Example 9 Solubility before modification 0.35 Solubility after modification 0.010

[0187] 2. Stir 65g acrylic emulsion, 35g APP powder, and 2.0g xanthan gum thickener for 10 minutes, and apply it on a 20cm×20cm 4g cloth, with a glue amount of 7-8g. Dry at 120℃ for 20 minutes, take it out, and soak it in 80℃ water for 4 hours with pure water. Measure the coating loss rate (the glue amount after coating is the total mass), flame retardancy, and observe whether there is any trace of powder precipitation on the coating surface. The results are shown in Table 2 and Table 3.

[0188] Table 2 Flame retardancy and precipitation resistance

[0189]

[0190] Table 380℃ solubility

[0191]

[0192] By comparing Examples 1 to 10 with Comparative Examples 1, 2, 3, and 9, it can be seen that the degree of polymerization of the product of the embodiment is much higher than that of the comparative example, and is also higher than the ammonium polyphosphate APP currently sold on the market; by comparing Examples 1 to 10 with Comparative Examples 4 to 9, it can be seen that the APP prepared based on the scheme constructed by the present invention has a significantly higher solubility than the comparative example. By comparing Examples 1 to 10 with Comparative Example 9, it can be seen that not only the degree of polymerization of the product of the embodiment scheme is high, but under the same modification conditions, although the solubility of the product of the comparative example is also relatively low, it is still higher than that of Examples 1 to 10 of the present invention.

[0193] Further through the comparison of application experiments, it can be seen that the product prepared by the present invention can withstand 80°C hot water immersion for 4 hours, the product loss rate is very low, and there is no trace of precipitation, while the comparative product has a large precipitation amount. Then we tested the solubility of the product at 80°C. The test results show that the solubility of the product prepared by the present invention at 80°C is much lower than that of Comparative Examples 4, 5, and 6 (Table 3), proving that the coating scheme of the present invention can indeed significantly improve the water resistance of APP; compared with Comparative Example 9, it is proved that even if the product implements the same coating scheme, due to the higher degree of polymerization of the product prepared by the present invention, it is more water-resistant than the ordinary type II ammonium polyphosphate product (Comparative Example 9).

[0194] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for synthesizing heat-resistant ammonium polyphosphate having ultrahigh polymerization degree, characterized in that: The following steps are involved: (1) Preparation of ammonium polyphosphate S1. First step reaction: Mix phosphorus pentoxide and diammonium hydrogen phosphate, stir and react at 200-250℃ for 1-3h, and then heat to less than 4m 3 / h of ammonia gas is introduced, and the reaction is continued for not less than 6h; wherein, the ammonia gas is introduced in two stages, and the ventilation volume in the first stage is 1 / 4 to 1 / 3 of that in the second stage; S2, second step reaction: phosphoric acid and melamine are mixed, reacted at 200-220°C for 0.5-1h, phosphoric acid is then added, and the reaction is continued at 220-250°C with stirring for 1.5-2h; S3, when the temperature in the first step reaction rises to 280-300°C, stop introducing ammonia, add the product of the second step reaction to the first step reaction, add diammonium hydrogen phosphate, and continue to react for 4-10 hours by introducing ammonia; (2) End-capping The prepared ammonium polyphosphate is end-capped with a coupling agent having an epoxy group; (3) Pre-curing A coupling agent with amino group is used as a curing agent, and after mixing it with the blocked ammonium polyphosphate and waterborne epoxy resin, it is heated at 40-45°C to complete pre-curing; (4) Coating The epoxy resin and the curing agent are mixed and dissolved, and then coated on the surface of the pre-cured ammonium polyphosphate. After the solvent evaporates, a drying process is performed to obtain the super-high polymerization degree and heat-resistant ammonium polyphosphate.

2. The synthesis method according to claim 1, characterized in that In step S1, the mass ratio of phosphorus pentoxide to diammonium hydrogen phosphate is 1:1 to 1:

3.

3. The synthesis method according to claim 1, characterized in that The introduction of ammonia in step S1 is divided into two stages. The first stage is the initial 0.5 to 1 hour of introduction of ammonia, followed by the second stage of introduction of ammonia.

4. The synthesis method according to claim 3, characterized in that The amount of ammonia introduced in the first stage is 0.8~1.2m 3 / h, the amount of ammonia introduced in the second stage is 3~3.5m 3 / h.

5. The synthesis method according to claim 3 or 4, characterized in that: The amount of ammonia introduced in step S3 is 3-3.5 m 3 / h, which is consistent with the ammonia introduction amount in the second stage in step S1.

6. The synthesis method according to claim 1, characterized in that The phosphoric acid initially added in step S2 is 10-15% of the mass of the phosphorus pentoxide in step S1, and the molar ratio of phosphoric acid to melamine is 1:2-3.

7. The synthesis method according to claim 1 or 6, characterized in that: The amount of phosphoric acid added in step S2 is the same as the amount of phosphoric acid initially added.

8. The synthesis method according to claim 1, characterized in that The process of end-capping is: The APP powder is capped by adding a coupling agent with epoxy groups in an amount of 1 to 2% of the total mass of the APP powder.

9. The synthesis method according to claim 1, characterized in that The epoxy resin used in step (4) is tetraepoxycyclohexylcyclosiloxane or AG-80; and the curing agent is a polyamide curing agent.

10. A heat-resistant ammonium polyphosphate having an ultra-high degree of polymerization, characterized in that: The method according to any one of claims 1 to 9 is used for synthesis.

Citation Information

Patent Citations

  • Method for preparing aminosilane coupling agent modifying ammonium polyphosphate

    CN101235221A

  • Method for preparing core-shell silicon dioxide-coated ammonium polyphosphate (APP)

    CN101760049A

  • Preparation method of core-shell type silicon dioxide coated nano calcium carbonate

    CN113549341A

  • Quaternary ammonium salt surface-modified ammonium polyphosphate

    US5071901A

  • Ammonium polyphosphate microencapsulated with amino-plastic resins

    US5576391A

Cited By

  • Preparation method and application of ammonium polyphosphate with high viscosity stability and low hygroscopicity

    CN122725222A